2011
DOI: 10.1016/j.ajo.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Axial Length and Outcomes of Macular Hole Surgery Assessed by Spectral-Domain Optical Coherence Tomography

Abstract: Axial length of 30.0 mm or more may increase the risk of anatomic failure of macular hole surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…The closure rate of 87.5 % was almost equal to the result of Eckardt et al in which they used similar methods as ours (Eckardt et al, 2008). In previous studies, it has been reported that the prognostic factors of macular hole surgery were the stage of macular hole, hole diameter, age of the macular hole and axial length (Ellis et al, 2000;Suda et al, 2011;Ullrich et al, 2002;Wells & Gregor, 1996). There were two cases required prone positioning over 3 days in this study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The closure rate of 87.5 % was almost equal to the result of Eckardt et al in which they used similar methods as ours (Eckardt et al, 2008). In previous studies, it has been reported that the prognostic factors of macular hole surgery were the stage of macular hole, hole diameter, age of the macular hole and axial length (Ellis et al, 2000;Suda et al, 2011;Ullrich et al, 2002;Wells & Gregor, 1996). There were two cases required prone positioning over 3 days in this study.…”
Section: Discussionsupporting
confidence: 64%
“…One case was an old (5 years) and large hole (870 µm) and the other was also an old hole (15 years). In order to increase closure rates more, it might be better to use long-acting gas as tamponade material for keeping macular region dry for longer time and perform the additional treatment such as retinal stretch in cases which have bad prognostic factors, such as large diameter or long axial length (Wells & Gregor, 1996;Suda et al, 2011). We assume hole closure once there is connection of hole edges.…”
Section: Discussionmentioning
confidence: 99%
“…Despite similar surgical approaches, the anatomical outcome after vitrectomy may be very different from series to series. [25][26][27][28][29] Although it has been shown that longer axial length is associated with more severe traction maculopathy and poorer surgical anatomic outcome, 30 the case number is too small to provide meaningful statistical analysis on risk factors of persistent MH.…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical closure is not achieved after a single operation in all cases, and patients with long-standing MHs [2] or highly myopic eyes [3] are challenging to treat. Moreover, a flat/open shape is observed postoperatively in 19-39% of all MHs, and this configuration is related to a worse visual acuity [4,5] .…”
Section: Introductionmentioning
confidence: 99%